Pathophysiologic Mechanisms and Serological Resolution Strategies for Cold Agglutinin-Mediated ABO Grouping Discrepancies in Transfusion Medicine : Clinical Ramifications and Operational Considerations A Narrative Review - Elvi Noviana (Lembaga Pengembangan Kinerja Dosen, 2026)
Cold agglutinin-mediated ABO grouping discrepancies pose persistent diagnostic and operational challenges in transfusion medicine. Cold-reactive autoantibodies, predominantly IgM with complement-binding capacity, cause false agglutination during forward and reverse grouping, potentially delaying crossmatching and jeopardizing transfusion safety. These issues are particularly relevant in laboratories with variable automation, such as in Indonesia, where manual methods remain common. This narrative review synthesized literature retrieved from electronic databases (Google Scholar, ScienceDirect, Scopus, and PubMed) on the pathophysiology, serological identification, and laboratory resolution strategies of cold agglutinin-mediated ABO grouping discrepancies, with emphasis on diagnostic, clinical, and operational implications across laboratory settings. Cold agglutinins cause spurious ABO grouping results through temperature-dependent erythrocyte agglutination and complement activation. Identification involves direct antiglobulin testing, saline replacement, and prewarming. Resolution requires warm-phase techniques, monospecific antisera, and adsorption/elution studies. Operationally, prolonged turnaround time, increased reagent use, and workflow strain have been reported, especially in resource-limited laboratories. Timely recognition and structured management of cold agglutinin-mediated discrepancies are essential to maintain transfusion accuracy. Implementation of standardized protocols, competency-based training, and evidence-based national guidelines can optimize patient safety and operational efficiency across varying healthcare infrastructures.”